Neuropsychological assessment of sport-related concussion - Johnson, E. W.; Kegel, N. E.; Collins, M. W. (Clinics in Sports Medicine, 2011)
Assessment of concussion can be challenging for medical practitioners given the different factors associated with each individual injury. The use of neuropsychological testing provides an objective method in the evaluation and management of concussion. Over the last 20 years it has become increasingly useful in the realm of sports concussion and has been deemed a cornerstone of concussion management by the Concussion in Sport group at the International Symposia on Concussion in Sport. Neuropsychological assessment has evolved to using computer-based neurocognitive testing, which has become increasingly common over the last decade, especially in organized sports. Neuropsychological assessment has also proven to be effective in the detection of differences based on several individual factors, including age, gender, and history of prior concussion. Despite its documented value, neuropsychological assessment should be one of several tools used as part of the concussion assessment/management process.